Pengaruh Media Booklet terhadap Pengetahuan Ibu Hamil mengenai Persiapan Persalinan - Elsa Putri Mardiani; Wisdyana Saridewi; Yeni Rosyeni (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Childbirth is a natural process that all pregnant women will experience. To avoid abnormal labor if complications occur during labor, good childbirth preparation is needed. The role of the media is very important in conveying information, one of which is using booklet media. The aim of this research was to determine the effect of booklet media in increasing the knowledge of third trimester pregnant women in the Batujajar Public Health Center, West Bandung Regency.The research design used Quasi Experimental Design, the research design used Control Group Design pre-test post-test. The sample from this study used a purposive sampling technique with 48 third trimester pregnant women at the Batujajar Community Health Center, West Bandung Regency. Primary data collection used a questionnaire instrument with experimental group intervention and control group. Univariate and bivariate analysis was carried out using the Wilcoxon Sign Rank Test and Mann Whitney.The research results showed that the level of knowledge of respondents before being given the intervention using booklet media, pregnant women had knowledge with a median score of 66.00 and after being given booklet media, pregnant women had increased knowledge with a median score of 95.00. There was a significant influence in the use of booklet media on increasing pregnant women's knowledge regarding childbirth preparation with p value = 0.001. Community health centers and health workers can use booklets as accompanying media for KIA books to increase pregnant women's knowledge to the maximum.